2021
DOI: 10.1039/d1nr05774j
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional transition metal borides as high activity and selectivity catalysts for ammonia synthesis

Abstract: In comparison to defect/doping induced activity in materials, transition metal borides with exposed metal atom, large specific surface area and high active site density show advantages as durable and efficient...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Similarly, Wen and co-workers theoretically examined six MB (M = Sc, Ti, V, Cr, Mo and W) monolayers for N 2 fixation, where VB ( U L = −0.40 V), CrB ( U L = −0.28 V), and MoB ( U L = −0.40 V) monolayers were screened out as efficient eNRR catalysts . Also, Wei and co-workers reported that the ReB 2 monolayer with a U L of only −0.05 V is a highly appealing catalyst for eNRR, emerging as a new class of TMB 2 materials . A specific computational study of Mo 2 B 2 by Wang et al revealed its feasibility as an eNRR catalyst with a low U L of −0.50 V…”
Section: Computation-assisted Catalyst Design For Enrrmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Wen and co-workers theoretically examined six MB (M = Sc, Ti, V, Cr, Mo and W) monolayers for N 2 fixation, where VB ( U L = −0.40 V), CrB ( U L = −0.28 V), and MoB ( U L = −0.40 V) monolayers were screened out as efficient eNRR catalysts . Also, Wei and co-workers reported that the ReB 2 monolayer with a U L of only −0.05 V is a highly appealing catalyst for eNRR, emerging as a new class of TMB 2 materials . A specific computational study of Mo 2 B 2 by Wang et al revealed its feasibility as an eNRR catalyst with a low U L of −0.50 V…”
Section: Computation-assisted Catalyst Design For Enrrmentioning
confidence: 99%
“…361 355 Also, Wei and coworkers reported that the ReB 2 monolayer with a U L of only −0.05 V is a highly appealing catalyst for eNRR, emerging as a new class of TMB 2 materials. 411 A specific computational study of Mo 2 B 2 by Wang et al revealed its feasibility as an eNRR catalyst with a low U L of −0.50 V. 261 4.1.4. TM Active Sites Anchored on 2D Materials.…”
Section: Dmentioning
confidence: 99%
“…However, it is difficult to improve the yield and Faraday efficiency of NRR simultaneously with that of a single-atom catalyst, mainly because NRR involves multiple protonation processes and many intermediates. To solve these problems, homonuclear metal double-atom catalysts for nitrogen fixation have been proposed, namely, Mn 2 @ g -C 2 N, Mo 2 @ g -C 2 N, Fe 2 N 4 @G, bi-Ti 3+ @TiO 2 , ReB 2 , and VN 4 duo@G . Unfortunately, the enhancement of catalytic performance by homonuclear metal double-atom catalysts is relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to improve the yield and Faraday efficiency of NRR simultaneously with that of a single-atom catalyst, mainly because NRR involves multiple protonation processes and many intermediates. To solve these problems, homonuclear metal double-atom catalysts for nitrogen fixation have been proposed, namely, Mn 2 @g-C 2 N, 23 Mo 2 @g-C 2 N, 24 Fe 2 N 4 @ G, 25 bi-Ti 3+ @TiO 2 , 26 ReB 2 , 27 and VN 4 duo@G. 28 Unfortunately, the enhancement of catalytic performance by homonuclear metal double-atom catalysts is relatively limited. Under the guidance of natural nitrogenase structure (including FeMo protein), 29 heteronuclear metal double-atom catalysts, such as M 1 M 2 @g-C 3 N 4 , 30 PdNb@Black Phosphorus, 31 M 1 M 2 @N-doped graphene, 32 AuNi@N-doped carbon, 33 FeRh@NPG, 34 and so on, 35−37 which reduces the Faraday efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…By using microkinetic modeling, the steady-state TOF of N 2 reduction to NH 3 can be calculated. We refer to previous work [117][118][119][120][121][122][123] to calculate the temperature-dependent pre-exponentials and rate constant and to set partial pressures of the reactant and product. The phase diagrams of TOF, temperature and pressure are shown in Fig.…”
Section: Paper Pccpmentioning
confidence: 99%